Synthesis of ETS-10-like vanadosilicates using 2,6-dimethylpiperidinium cation derivatives as organic templates - Contro, Janine [UNESP]; Paula, Alex S. [UNESP]; Medeiros, Vinicius Litrenta [UNESP]; Rodrigues, Ariano D.; Pacheco, Carlos; Nery, José G. [UNESP] (Elsevier, 2020)
Systematic vanadosilicate syntheses were performed using derivatives of 2,6-dimethylpiperidine as organic structure-directing agents (SDAs). Physicochemical analyses of the vanadosilicate materials obtained were carried out by X-ray diffraction (XRD), Raman spectroscopy, infrared (IR) spectroscopy, UV–visible (UV–Vis) spectroscopy, and solid-state NMR spectroscopy (29Si and 51V MAS NMR). The experimental results indicated that the presence of the organic templates had different effects on the final phases of the synthesized vanadosilicates. The XRD results showed that 1,1,2,6-tetramethylpiperidinium (SDA 1) favored synthesis of the known AM-6 vanadosilicates, isostructural to the ETS-10 titanosilicate, while the other organic templates 1,1-diethyl-2,6-dimethylpiperidinium (SDA 2), 6,10-dimethyl-5-azoniaspiro[4.5]decane (SDA 3), and 1,5-dimethyl-6-azoniaspiro[5.5]undecane (SDA 4) directed the formation of vanadosilicates with different phases, such as EVS-10. Strong Raman bands at 870 and 1035 cm−1 indicated vibrational modes associated with the highly symmetric vanadia octahedra. Chemical shifts at −96 ppm (29Si MAS NMR), −610, and −570 ppm (51V MAS NMR) provided further evidence of the incorporation of vanadium into the structures of the vanadosilicates prepared using these novel derivatives of 2,6-dimethylpiperidinium cations as SDAs.
Keywords: 2,6-Dimethylpiperidinium cation; Solid-state MAS NMR; Structure-directing agent; Vanadosilicates